The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s40561-015-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Can a kitchen teach languages? Linking theory and practice in the design of context-aware language learning environments

Abstract: Smart learning environments offer rich opportunities for language learners. In particular, context-aware systems which allow learners' progress to be sensed within and across an activity, enable instructed language learning to move beyond the traditional confines of the classroom walls. In this paper we present the European Kitchen, a real-world task-based environment for cooking and language learning. In doing so, we demonstrate how specific design decisions, in the development of this longer-term iterative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…Further, the mean difference between the posttest and delayed test was 7.58, which indicated that the participants still retained and retrieved the information they had learned 2 weeks after the posttest. This finding confirms those reported by several previous studies that situating students in real‐world contexts with ubiquitous supports via mobile and wireless communication technologies can encourage them to learn and practice actively and constantly, and hence improve their learning outcomes, in particular for language learning (Liu et al, ; Preston et al, ; Wong, King, Chai, & Liu, ). The results of the pretest, posttest and delayed test differed significantly, F (2,107) = 34.761, p <.001.…”
Section: Resultssupporting
confidence: 90%
“…Further, the mean difference between the posttest and delayed test was 7.58, which indicated that the participants still retained and retrieved the information they had learned 2 weeks after the posttest. This finding confirms those reported by several previous studies that situating students in real‐world contexts with ubiquitous supports via mobile and wireless communication technologies can encourage them to learn and practice actively and constantly, and hence improve their learning outcomes, in particular for language learning (Liu et al, ; Preston et al, ; Wong, King, Chai, & Liu, ). The results of the pretest, posttest and delayed test differed significantly, F (2,107) = 34.761, p <.001.…”
Section: Resultssupporting
confidence: 90%
“…Our data originate from the European Union‐funded research and developmental project Learning Languages, Cultures and Cuisines in Digital Interactive Kitchens (LanCook; see Kurhila & Kotilainen, 2020; Preston et al., 2015; Seedhouse, 2017). The LanCook ‘kitchen’ contains a computer program and motion sensors.…”
Section: Datamentioning
confidence: 99%
“…Com relação ao sentido do tato, podemos citar pesquisas e trabalhos sobre aspectos mais sinestésicos da aprendizagem de línguas, como o ensino de vocabulário por meio de atividades lúdicas que envolvem esse e outros sentidos (ver, por exemplo, AJAYI, 2018; HELLMAN, 2018). E até mesmo o paladar tem sido pesquisado nas salas de aula de aprendizagem de línguas por meio de aulas práticas de culinária e degustação como parte da prática dos alunos (ver, nesse caso, FELDER;HENRIQUES, 1995;PRESTON et al, 2015). No entanto, na opinião do pesquisador, o olfato ainda é um dos sentidos humanos que carece de pesquisas sobre aprendizagem de línguas a ele relacionadas.…”
Section: Os Sentidos Nas Narrativas: Tornando-se Professores De Inglêsunclassified